The role of HLA LOH in the development of Asian liver cancer - Phua, Cheryl Zi Jin (2018)
Immune evasion is one hallmark of cancer, whereby the immune system is unable to recognize and target tumors for destruction. Immunotherapy is a promising emerging treatment that has high potential to counteract immune evasion. However, its effectiveness is limited in liver cancer treatment due to lack of understanding of the mechanisms underlying immune evasion. Loss of heterozygosity (LOH) at the human leukocyte antigen (HLA) may be important in the development of immune evasion, as HLA is crucial in neoantigen presentation for the effective initiation of an immune response. We characterized the effects of HLA LOH in liver cancer with regards to cytolytic activity, TCR diversity, as well as potential association with mutational signatures and its timing in tumor development. We found that tumors exhibiting HLA LOH were present in 66.7% of patients, and were associated with higher cytolytic activity, greater TCR diversity and aging mutational signatures. HLA LOH was found to occur mostly at the subclonal level. Hence, HLA LOH may have developed primarily in late stage tumors as an escape mechanism to circumvent a stronger anti-tumor immune response due to higher neoantigen burden. These findings may refine our understanding of immune resistance and have implications for future immunotherapeutic approaches.